Impact of levels of residue retention on soil properties under conservation agriculture in Vertisols of central India. Issue 3 (23rd February 2022) - Kumawat, Anita; Vishwakarma, A.K.; Wanjari, R.H.; Sharma, N.K.; Yadav, Devideen; Kumar, Dinesh; Biswas, A.K.
ABSTRACT: Residue management is one of the most difficult tasks in the modern-mechanized agriculture with the intensification of cropping systems, which leads to reduced sowing window between two crops and farmers prefer in-situ burning of crop residues. Therefore, the present study was conducted to assess the effect of zero tillage (ZT) based residue management on soil health parameters in maize ( Zea mays L.)–chickpea ( Cicer arietinum L.) rotation in black soils of central India. After 4 years of study, the soil bulk density was reduced by 3.0–10.2% and volumetric moisture content was improved by 10.2–19.3% at 0–10 cm soil depth in ZT with residue over conventional tillage (CT). The soil organic carbon and labile carbon were increased by 13.6–61.7% and 6.0–22.0%, respectively, at 0–10 cm soil depths. Similarly, ZT with residue increased the KMnO4 -N, Olsen-P and NH4 OAc-K, and total fungal and actinomycetes density in surface soil as compared to CT. Thus, our study advocates that ZT with residue retention (1.8–5.4 Mg ha –1 maize and 0.8–2.4 Mg ha –1 chickpea residue) should be implemented for sustainable soil health in Vertisols (Typic Haplustert) of central India and other similar agro-ecological systems.